Motion compensated video coding - Garnham, Nigel William (1995)
The result of many years of international co-operation in video coding has been the development of algorithms that remove interframe redundancy, such that only changes in the image that occur over a given time are encoded for transmission to the recipient. The primary process used here is the derivation of pixel differences, encoded in a method referred to as Differential Pulse-Coded Modulation (DPCM)and this has provided the basis of contemporary research into low-bit rate hybrid codec schemes. There are, however, instances when the DPCM technique cannot successfully code a segment of the image sequence because motion is a major cause of interframe differences. Motion Compensation (MC) can be used to improve the efficiency of the predictive coding algorithm.